Islamic Science Camp: Program Pembelajaran IPA yang Menyenangkan dengan Konsep Islami dan Kecintaan pada Alam - Ro’i Khatul Jannah; Muhamad Imaduddin; Muhammad Fathurriza; Muhammad Ali Sofyan; Helmi Auliya; Atmim Nurona; Izzatul Ulya; Abu Choir (Journal of Natural Science and Integration, 2021)
This study aims to reveal how the concept of learning program design at the Islamic Science Camp (ISC), as well as to show the impressions of children and parents on the various ISC activities. This research consists of three stages, namely define, design and development. The trial subjects came from 11 elementary school (Islamic) institutions consisting of 28 students. The data were collected using (1) observation checklists; (2) documentation; (3) field notes sheets; and (4) impression sheets. Data analysis used tabulation techniques, narrative descriptions, and word cloud analysis. The science topics tested were related to (1) changes in the form of substances; (2) the concept of force and pressure; (3) matter and its classification; (4) the concept of energy; (5) aquatic ecosystems; and (6) plant morphology. Islamic values are emphasized in directing children's habituation activities, as well as providing children's motivation through Islamic figures in the fields of science and technology. Science projects include (1) a rotary ice cream making project; (2) launching a water rocket project; (3) making air freshener; (4) studying Islamic science; (5) building a ship and launching it; (6) river tracing and fishing; (7) making key chains from resin; and (8) making ecoprinting using pounding technique. Various positive impressions were obtained from the children and parents involved, and on the sustainability aspect, it was shown that there were repetitions and follow-up experiments by children outside the ISC program.Keywords: islamic science camp, science learning, love of nature, islamic science concept. ABSTRAK Kajian ini bertujuan untuk mengungkap bagaimana konsep desain program pembelajaran pada Islamic Science Camp (ISC), serta menunjukkan kesan anak dan orang tua pada ragam akivitas ISC. Riset ini terdiri dari tiga tahapan yaitu define, design, dan development. Subyek uji coba berasal dari 11 instansi SD/MI yang terdiri dari 28 siswa. Pengumpulan data menggunakan (1) daftar cek observasi, (2) dokumentasi, (3) lembar catatan lapangan, dan (4) lembar kesan. Analisis data menggunakan teknik tabulasi, deskripsi naratif, serta word cloud analyisis. Topik IPA yang diujicobakan berkaitan dengan (1) perubahan wujud zat; (2) konsep gaya dan tekanan; (3) materi dan klasifikasinya; (4) konsep energy; (5) ekosistem perairan; dan (6) morfologi tumbuhan. Nilai-nilai Islam ditekankan pada pengarahan kegiatan habituasi anak, serta pemberian motivasi anak melaui tokoh-tokoh Islam bidang sains dan teknologi. Proyek sains mencakup (1) proyek pembuatan es krim putar; (2) proyek meluncurkan roket air; (3) pembuatan pengharum ruangan; (4) kajian sains islami; (5) proyek pembuatan kapal dan meluncurkannya; (6) susur sungai dan tangkap ikan; (7) pembuatan gantungan kunci dari resin; dan (8) pembuatan ecoprinting dengan teknik pounding. Beragam kesan positif diperoleh dari anak dan orang tua yang terlibat, serta pada aspek keberlanjutan ditunjukkan adanya repetisi dan eksperimen lanjutan oleh anak di luar program ISC. Kata kunci: Islamic Science Camp, pembelajaran IPA, cinta alam, konsep islami sains.